Entrenched in context: Perceptions regarding intimate partner violence and viable interventions among undergraduate students - Montanez, Julio (2015)
Many policies and programs have relevance to intimate partner violence (IPV), such as no-drop policies, firearm-related policies, mandatory reporting, mandatory arrest, and others. IPV affects persons from a multitude of demographics and statuses. Dating violence has its mark on college campuses. The present research studies both attitudes toward IPV and attitudes toward interventions that pertain to IPV. Attitudes toward IPV have been found to relate to a number of explanatory variables: attributions, socioeconomic status, age, class standing, race/ethnicity, religion/spirituality, attitudes toward gender, violence in the family of origin, and previous IPV histories. Perceptions of IPV interventions have been found to relate to a number of explanatory variables as well: attitudes toward IPV, attributions, race/ethnicity, gender, age, socioeconomic status, education victim status, sexual orientation, attitudes regarding gender, and political variables. The present research administered a survey to undergraduate students at the University of Central Florida as a means to explore such perceptions